Intramolecular hydrogen transfer in DNA induced by site-selective resonant core excitation. Issue 13 (17th March 2022) - Wang, Xin; Rathnachalam, Sivasudhan; Zamudio-Bayer, Vicente; Bijlsma, Klaas; Li, Wen; Hoekstra, Ronnie; Kubin, Markus; Timm, Martin; von Issendorff, Bernd; Lau, J. Tobias; Faraji, Shirin; Schlathölter, Thomas
Abstract : We present experimental evidence for soft X-ray induced intramolecular hydrogen transfer in the protonated synthetic tri-oligonucleotide d ( F UAG) in the gas-phase ( F U: fluorouracil). Abstract : We present experimental evidence for soft X-ray induced intramolecular hydrogen transfer in the protonated synthetic tri-oligonucleotide d ( F UAG) in the gas-phase ( F U: fluorouracil). The trinucleotide cations were stored in a cryogenic ion trap and exposed to monochromatic synchrotron radiation. Photoionization and photofragmentation product ion yields were recorded as a function of photon energy. Predominanly glycosidic bond cleavage leading to formation of nucleobase-related fragments is observed. In most cases, glycosidic bond cleavage is accompanied by single or double hydrogen transfer. The combination of absorption-site-sensitive soft X-ray spectroscopy with fragment specific mass spectrometry allows to directly relate X-ray absorption site and fragmentation site. We observe pronounced resonant features in the competition between single and double hydrogen transfer towards nucleobases. A direct comparison of experimental data with time-dependent density functional theory calculations, using short range corrected hybrid functionals, reveal that these hydrogen transfer processes are universal and not limited to population of particular excited states localized at the nucleobases. Instead, hydrogen transfer can occur upon X-ray absorption in any nucleobase and in the DNA backbone. Resonances seem to occur because of site-selective suppression of hydrogen transfer channels. Furthermore, non-covalent interactions of the optimized ground state geometries were investigated to identify intramolecular hydrogen bonds along which hydrogen transfer is most likely.